Answer:
x = - 2, x =
![(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/810xodspel5mrswej0fay1vvz0sburw3kp.png)
Explanation:
Given
2x² + x - 6 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 2 × - 6 = - 12 and sum = + 1
The factors are + 4 and - 3
Use these factors to split the x- term
2x² + 4x - 3x - 6 = 0 ( factor the firs/second and third/fourth terms )
2x(x + 2) - 3(x + 2) = 0 ← factor out (x + 2) from each term
(x + 2)(2x - 3) = 0
Equate each factor to zero and solve for x
x + 2 = 0 ⇒ x = - 2
2x - 3 = 0 ⇒ 2x = 3 ⇒ x =
![(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/810xodspel5mrswej0fay1vvz0sburw3kp.png)